A new species and three hybrids in the ferns from Cocos Island, Puntarenas, Costa Rica - Rojas-Alvarado, Alexander Francisco (Universidad de Málaga. Servicio de Publicaciones e Intercambio Científico, 2017)
A new species and three new hybrids of ferns from the Cocos Island (Costa Rica) are described here: Cyathea × robusta A. Rojas, Elaphoglossum × intermedium A. Rojas, Nephrolepis cocosensis A. Rojas and Tectaria × epilithica A. Rojas. The new species differs from Nephrolepis rivularis (Vahl) Mett. ex Krug by its terrestrial habitat, smaller fronds, smaller pinnae that are perpendicular to rachis and lobed to bilobed distally, pale brown rachis scales with dark brown insertion points, blade scales 0.2–0.4 mm in diameter, sometimes reduced to a resinous dots, sori submarginal, frequently in the internal lobe of each segments, and indusia cordiform and basally attached, pale brown with dark brown point of attachment. The first hybrid is intermediate between Cyathea alfonsiana L.D. Gómez and C. notabilis Domin, in trunk tall, size and form of rhizome and stipe scales, fronds size, pairs per segment and division degree of veins and paraphyses size, but has bigger fronds that both progenitors, this character is the basis for its specific epithet. Elaphoglossum x intermedium is a hybrid between E. alvaradoanum A. Rojas and E. crinitum (L.) Christ and is characterized by brown stipe and blade scales, cuneate blade base an obtuse blade apex, and veins partially and irregularly anastomosing. Tectaria x epilithica has intermediate characters between T. incisa Cav. and T. mexicana (Fée) C.V. Morton, this hybrid is easy to recognize because has 1-pinnate-pinnatifid blade and possesses rhizome scales that are intermediate in size compared to those of its parents.
Una nueva especie y tres híbridos en helechos para la Isla del Coco, Puntarenas, Costa Rica
Keywords: Helechos - Costa Rica; Cyathea; Elaphoglossum; Especies nuevas; Híbridos nuevos; Nephrolepis; Tectaria